Effects of Habitat Change on the Web Characteristics and Fitness of the Giant Wood Spider (Nephila pilipes) in Sri Lanka - Wijerathna, Tharaka; Tharanga, Dilini; Perera, Inoka C.; Wijesinghe, Mayuri R. (International Journal of Zoology, 2019)
We compare web properties and fitness of the Giant wood spider Nephila pilpes within and outside its natural rainforest habitat in Sri Lanka. The nonforest habitats comprised rural home gardens and plantations. We hypothesize that marked differences would be evident between the two habitats in (i) web properties and (ii) fitness of the female spiders. Web architectural and silk thread properties were measured in 25 webs of adult female spiders in each of the two habitats, while female abdomen size was used as the proxy for fitness. Findings support both hypotheses. The nonforest webs were more closely knit (smaller mesh spaces) and the hub was placed at higher position on the web than that in the forest webs both altering prey capture efficiency. Also, females in nonforest habitats were significantly smaller than those in the forest, indicating lowered fitness. The disparities in web characteristics and fitness are impressive given that the forest and nonforest habitats are located in close proximity, suggesting that rainforest orbweaver spiders such as Nephila pilpes may suffer population declines if the extents of natural forest continue to shrink.